Peran Pengawas Sekolah Dalam Meningkatkan Kualitas Pendidikan di SMA Kabupaten Murung Raya - Asmarinda, Asmarinda (ANTHOR: Education and Learning Journal, 2022)
This paper discusses the role of school supervisors in improving the quality of education in SMA. In its discussion, this paper describes the duties and responsibilities of school supervisors and the factors that affect the quality of education in SMA. In the duties and responsibilities of school supervisors, it is emphasized that school supervisors must be able to provide effective and efficient supervision, guidance, and supervision of teachers and students. In addition, school supervisors must also be able to develop adaptive and innovative supervision programs in accordance with the times and the needs of high schools. The factors that influence the quality of education in SMA discussed in this paper includeinternal and external factors. Internal factors such as school management, teachers, curriculum, and school facilities and infrastructure. While external factors such as sociocultural, economic, and political conditions. This paper also discusses strategies that can be implemented by school supervisors in improving the quality of education in SMA. Some of the strategies described in this paper include developing teacher competence, using technology in learning, good management of school facilities and infrastructure, and providing intensive guidance and supervision to students. From this discussion, it can be concluded that the role of school supervisors is very important in improving the quality ofeducation in SMA. Therefore, school supervisors must be able to carry out their duties and responsibilities properly and develop effective and efficient strategies to improve the quality of education in SMA.